PENGARUH PEMBELAJARAN VIDEO IMERSIF INTERAKTIF TERHADAP MOTIVASI MURID DALAM PEMBELAJARAN PJOK DI SEKOLAH DASAR - Anjasmoro, Daud; Wibowo, Sapto; Priambodo, Anung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Motivation is closely related to the level of student learning engagement, focus, and success in school. In this study, the researcher used a quasi-experimental quantitative design. This study used a pretest-posttest control-group design involving 5th-grade students from Ketajen 1 Public Elementary School in Sidoarjo Regency. The researcher collected data using a learning motivation questionnaire that had been tested for validity and reliability. Data were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, the homogeneity test, the paired-samples t-test, and the independent-samples t-test. The normality test showed a p-value greater than 0.05, which means the data were normally distributed. The homogeneity test produced a p-value of 0.375 (above 0.05), which indicates that the data are homogeneous. The paired-samples t-test showed a significance value (2-tailed) of 0.000 for both groups, less than 0.05, indicating a difference between the pretest and posttest results in the experimental and control groups. The independent t-test also showed a significance value (2-tailed) of 0.000 (less than 0.05), indicating that learning using immersive video had a significant impact. In conclusion, learning Physical Education (PJOK) using immersive video can significantly increase student learning motivation.